Are There Long-Term Effects of the Vietnam Draft on Political Attitudes or Behavior? Apparently Not. Issue 2 (18th December 2018) - Green, Donald P.; Davenport, Tiffany C.; Hanson, Kolby
Abstract: The Vietnam draft lottery exposed millions of men to risk of induction at a time when the Vietnam War was becoming increasingly unpopular. We study the long-term effects of draft risk on political attitudes and behaviors of men who were eligible for the draft in 1969–1971. Our 2014–2016 surveys of men who were eligible for the Vietnam draft lotteries reveal no appreciable effect of draft risk across a wide range of political attitudes. These findings are bolstered by analysis of a vast voter registration database, which shows no differences in voting rates or tendency to register with the Democratic or Republican parties. The pattern of weak long-term effects is in line with studies showing that the long-term economic effects of Vietnam draft risk dissipated over time and offers a counterweight to influential observational studies that report long-term persistence in the effects of early experiences on political attitudes.